Novejši biooznačevalci in spremljanje znotrajceličnih signalnih poti pri avtoimunskih boleznih - Goropevšek, Aleš (Zdravniški vestnik, 2008)
Background. Almost all current therapeutic concepts in many autoimmune and chronic inflammatory diseases are based on the systemic suppression of immune functions and are not curative. Identification of cytokines TNF and IFN-alpha as major factors in the pathogenesis of diseases such as rheumatoid arthritis and systemic lupus erythematosus (SLE) represent a substantial improvement in understanding of autoimmune diseases. Intracellular signalling pathways that are activated in response to those clinically relevant cytokines, mediate signals through kinase phosphorylation of proteins and are at the core of immune cell function. However, little is known about their changes in autoimmune disease states. Recent trials emphasized the importance of directl yassessing the human immune responses, and that not all of what we learn for example in the mouse can be directly translated to humans. Thus, there is a need for the development of tools and assays to directly assess the human immune system, and to predict its responses to novel therapeutic entities. Newly discovered biomarkers represent promising tools. Even more promising are approaches, that are based on monitoring immune signaling on the single cell level. Conclusions. A series of assay systems for flow cytometric-based biochemical analysis at the single-cell level for kinase and phosphoprotein profiling have been developed. This will give us opportunity to study signal pathways also in autoimmune and chronic inflammatory diseases, as the analysing systems are adapted to immunocytes for example in peripheral blood. First results show characteristic phospho-signature of cytokines (interferons) in immune cells from SLE patients. Monitoring signaling pathways on the single cell level can lead to developments in new diagnostic tools, especially in monitoring of disease activity. Results can also identify new targets of more specific and less toxic therapy with kinase inhibitors.
Keywords: Autoimmune Diseases; Avtoimunske bolezni; biooznačevalci; Citokini; Cytokines; diagnostika; Flow Cytometry; imunosupresija; Interferon-alfa; Interferon-alpha; Lupus Erythematosus, Systemic; Pretočna citometrija; Sistemski lupus eritematozus; therapy; zdravljenje